2016
DOI: 10.1371/journal.pone.0151079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Literacy on Quality of Life amongst Patients with Ischaemic Heart Disease in Australian General Practice

Abstract: BackgroundAppropriate understanding of health information by patients with cardiovascular disease (CVD) is fundamental for better management of risk factors and improved morbidity, which can also benefit their quality of life.ObjectivesTo assess the relationship between health literacy and health-related quality of life (HRQoL) in patients with ischaemic heart disease (IHD), and to investigate the role of sociodemographic and clinical variables as possible confounders.MethodsCross-sectional study of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
58
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 42 publications
11
58
1
3
Order By: Relevance
“…Our results on the positive association between health literacy and physical HRQoL (PCS) most likely reflect the complex reality of many people with extensive physical health problems, where the demands placed on their health literacy may be multiple. These findings are consistent with several other studies in people with cardiac disease [13,19,42]. Strong associations were found in relation to actively engaging with healthcare providers and navigating the healthcare system (scales 6 and 7), that is, "executive capacities", which may reflect the many players and services that are often involved in the care of people with physical health challenges.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results on the positive association between health literacy and physical HRQoL (PCS) most likely reflect the complex reality of many people with extensive physical health problems, where the demands placed on their health literacy may be multiple. These findings are consistent with several other studies in people with cardiac disease [13,19,42]. Strong associations were found in relation to actively engaging with healthcare providers and navigating the healthcare system (scales 6 and 7), that is, "executive capacities", which may reflect the many players and services that are often involved in the care of people with physical health challenges.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, literature on general populations confirms strong associations between health literacy and mental HRQoL (MCS) [9,43]. Studies based on populations with cardiac disease are less conclusive [13,19]. However, none of these studies includes very comprehensive health literacy measures.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of our study were in the line of a study in the US, which confirmed the effect of HL on the health status and health services utilization among elderly people (30). The result of inadequate HL on a poor physical function dimension of quality of life among patient with ischemic heart disease is shown in a study in Queensland and South Australia (31). HL may lead to a better lifestyle (32,33), more use of preventive care (34), and adherence to medical treatment (35).…”
Section: Discussionsupporting
confidence: 86%
“…Despite the importance of communication skills training, little experimental research has linked skilled physician communication with patient HL and medical outcomes. Further, the interaction between HL skills development and health education interventions has not been well investigated [9,16] because it is unclear how/where physicians' communication skills can influence patient HL skills and medication adherence to control blood pressure targets [17,18]. Thus, there is an increasing need for assessments of strategies, which improve physician-patient communication quality, patient HL and health outcomes in the medical care context [11,19].…”
Section: Introductionmentioning
confidence: 99%